Comparative Study of Forward and Reverse Ion Exchange Reaction in Amberlite IRA -400 by Application of Tracer Isotope- 131I. - LOKHANDE, R.S.; SlNGARE., P.U. (Asian Journal of Chemistry, 2010)
Iodide ion exchange reaction between the resin and solution phase can be represented by RI + I*(aq) RI* + I(aq) where RI is the resin phase having exchangeable iodide ion, 1* is the radioactive 131I tracer isotope. This exchange of radioactive iodide ions and inactive iodide ions takes place reversibly. In the present investigation, kinetics study of forward and reverse ion exchange reaction was carried out in two sets of experiments: (1) exchange between radioactive iodide ions in solution and iodide ions on ion exchanger (forward exchange), (2) exchange between radioactive iodide ions on ion exchanger and iodide ions in solution (reverse exchange). This exchange study was performed at different temperatures from 27°C to 48°C, for different concentrations of potassium iodide solution from 0.0025 to 0.1 M and for different amounts of ion exchange resin ranging from 0.250 g to 5.00 g. The forward and reverse ion exchange reaction rates were observed to be 0.123 min-1 and 0.122 min-1 under identical conditions of 1 g ion exchanger at 27°C and 0.01 M iodide ion solution indicating that forward and reverse ion exchange reaction occurs simultaneously.